Gods and Robots: myths, machines and ancient dreams of technology - Mayor, Adrienne (Princeton University Press, 2018)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- List of Illustrations -- Acknowledgments -- INTRODUCTION. Made, Not Born -- 1 The Robot and the Witch: Talos and Medea -- 2 Medea's Cauldron of Rejuvenation -- 3 The Quest for Immortality and Eternal Youth -- 4 Beyond Nature: Enhanced Powers Borrowed from Gods and Animals -- 5 Daedalus and the Living Statues -- 6 Pygmalion's Living Doll and Prometheus's First Humans -- 7 Hephaestus: Divine Devices and Automata -- 8 Pandora: Beautiful, Artificial, Evil -- 9 Between Myth and History: Real Automata and Lifelike Artifices in the Ancient World -- EPILOGUE. Awe, Dread, Hope: Deep Learning and Ancient Stories -- Glossary -- Notes -- Bibliography -- Index